2014
DOI: 10.1063/1.4869457
|View full text |Cite
|
Sign up to set email alerts
|

Role of interface structure and chemistry in resistive switching of NiO nanocrystals on SrTiO3

Abstract: Nickel oxide (NiO) nanocrystals epitaxially grown on (001) strontium titanate (SrTiO3) single crystal substrates were characterized to investigate interface morphology and chemistry. Aberration corrected high angle annular dark field scanning transmission electron microscopy reveals the interface between the NiO nanocrystals and the underlying SrTiO3 substrate to be rough, irregular, and have a lower average atomic number than the substrate or the nanocrystal. Energy dispersive x-ray spectroscopy and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…From our previous observation using C-AFM, it has been shown that the conduction mechanism in the NiO/Nb:STO junction follows the Schottky emission process where vacancy concentration changes modulate the minority carrier density and hence barrier height at the interface . Moreover, detailed transmission electron microscopy (TEM) and electron energy loss spectrum (EELS) studies have revealed that the oxygen vacancies are preferably located at the NiO/Nb:STO interface and might be modulated by the electric field . Therefore, it should be expected that the oxygen vacancies at the edge of the nanocrystals can actively drive the switching performance.…”
Section: Morphology and Single-point Current–voltage Investigation Of...mentioning
confidence: 99%
“…From our previous observation using C-AFM, it has been shown that the conduction mechanism in the NiO/Nb:STO junction follows the Schottky emission process where vacancy concentration changes modulate the minority carrier density and hence barrier height at the interface . Moreover, detailed transmission electron microscopy (TEM) and electron energy loss spectrum (EELS) studies have revealed that the oxygen vacancies are preferably located at the NiO/Nb:STO interface and might be modulated by the electric field . Therefore, it should be expected that the oxygen vacancies at the edge of the nanocrystals can actively drive the switching performance.…”
Section: Morphology and Single-point Current–voltage Investigation Of...mentioning
confidence: 99%
“…Out of several types of memory, nonvolatile memory has been the most reliable in terms of maintaining data without external power. Recently, resistive switching random access memory (ReRAM) has become a dominant candidate for the nonvolatile memory application because of its fast switching speed, high integration density, low power consumption, nondestructive readout, and promising scalability. Moreover, the simple capacitor-like structure composed of an insulating layer between two metallic electrodes (MIM structure) , makes the fabrication simple. In the resistive memory device, the active layer usually changes its states from a high-resistive state (HRS) to a low-resistive state (LRS) and vice versa upon application of voltage amplitudes. , Depending on the polarity of the voltage required, the switching process is mainly categorized as bipolar and unipolar switching, corresponding to nonvolatile memory switching (MS).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most studies on resistive switching (RS) have focused on metal oxides, transition metal dichalcogenides, and perovskite oxides such as TiO 2 , NiO, SrTiO 3 , Pr x Ca 1– x MnO 3 , and so forth. ,, Recently, organic–inorganic halide perovskites with a chemical formula ABX 3 have gathered a great amount of attention because of their excellent performance in solar cells, photodetectors, light-emitting diodes, memories, and so forth. Halide perovskite offers exceptional compatibility as an active material in ReRAM because of defects and ion migration-mediated current voltage hysteresis . However, a halide perovskite comprising organic cations suffers from rapid degradation, originating from hygroscopicity and thermal instability, and limits its implication in electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the morphology of this surface reconstruction by itself appears very similar to the encapsulation/decoration phenomena observed from metal/metal oxide structured catalysis as part of the SMSI. In encapsulation the cations from substrate diffuse to the interface and nanoparticles are eventually covered by a thin layer of reduced substrate according to the following relationship: Although it is well-known noble metal nanoparticles on STO support have SMSI, we believe here the situation is closer to the case of the encapsulation/decoration phenomenon commonly observed for binary oxides such as titanium oxide (TiO 2 ) , and cerium oxide (CeO 2 ) surfaces. , In the case of NiO grown on STO substrate, we know previously that the surface of STO is reduced . Through careful and high-resolution electron energy loss spectra (EELS) analysis, we found that the interface has Ti with lower valence (+4−δ) than the stoichiometric value of +4, even for STO several layers away from the Ni–STO interface.…”
Section: Resultsmentioning
confidence: 72%